Selective electrochemical H2O2 production through two-electron oxygen electrochemistry - Jiang, Yuanyuan (2020)
Direct electrochemical production of hydrogen peroxide (H2O2) through two-electron oxygen electrochemistry, for example, the oxygen reduction in fuel cells or water oxidation in water electrolyzers, could provide an attractive alternative to locally produce this chemical on demand. The efficiency of these processes depends greatly on the availability of cost-effective catalysts with high selectivity, activity, and stability. In recent years, various novel nanostructured materials have been reported to selectively produce H2O2. Through combined experimental and theoretical approaches, underlying mechanisms in the electrochemical synthesis of H2O2 via oxygen electrochemistry have been unveiled. Considering the remarkable progress in this area, the authors summarize recent developments regarding the direct production of H2O2 through two-electron electrochemical oxygen reactions. The fundamental aspects of electrochemical oxygen reactions are first introduced. Various types of catalysts that can effectively produce H2O2 via two-electron oxygen electrochemistry are then presented. In parallel, the unique structure-, component-, and composition-dependent electrochemical performance together with the underlying catalytic mechanisms are discussed. Finally, a brief conclusion about the recent progress achieved in electrochemical generation of H2O2 and an outlook on future research challenges are given.